BANGRENG AS A MEANS OF SPREADING ISLAM - Sofian, Maylan (State Institute of Islamic Studies (IAIN) Palu, 2019)
Bangreng was originally an example used by the Sumedang community as a medium to express gratitude for everything that Allah SWT gave to humans. But the function of art as a ritual began to shift into art as entertainment. This bangreng art is an art that is very interesting to study because there are only a few different functions. This change does not change the name of the show. With this description, it needs to be isolated, that is, the community does not lose identity. Because if the identity is lost it will also disappear from the important to be studied. The aim is that the public knows the function of the nation in the spread of Islam. The method used in this study is using qualitative research design using the approach as a medium of bangreng music. From this research, it is expected that it can show the Bangreng as a means of removing Islam.